The Eurasian Economic Union in Search of Strategic Partners: The Gravity Effects of Integration Blocs - Garashchuk, Anna; Podadera-Rivera, Pablo; Isla-Castillo, Fernando (Savez ekonomista Srbije, 2023)
The present contribution aims at researching the new Eurasian project on the post-Soviet area, the Eurasian Economic Union, by analyzing the legal aspects of both its institutional and economic frameworks. Because of its relatively small size, not only should the Eurasian Economic Union increase bilateral trade with its member states but also promote commerce outside the Union. In this regard, the crucial objective for success is the development of long-term relationships with its strategic partners based on mutual economic benefits and shared values. We applied the gravity model and identified not only which factors influence bilateral foreign trade, including the differences in partners’ values based on a neo-institutional approach, but also analyzed those integration blocs and groups of countries to determine with which partners the Eurasian Economic Union should develop strategic partnerships.
Se trata de uno de los resultados de investigación basados en la línea de investigación para la realización de la Tesis Doctoral dirigida por el candidato y defendida por su coautora, titulada: “The role of the models of strategic partnership in the new world order. Euro-Russian relations and the Eurasian Economic Union in strategic perspective” (con calificación de Sobresaliente cum laude por unanimidad y Mención Internacional). Inspirado en la participación de los candidatos en el Congreso Internacional: 32nd Annual Conference of the European Association for Evolutionary Political Economy, Bilbao (2-4/09/2020) y organizado por la prestigiosa European Association for Evolutionary Political Economy, así como en aportaciones de los autores a otros congresos como: XIX Reunión de Economía Mundial / XIX World Economy Meeting (10-12/05/2017); XII Jornadas de Seguridad, Defensa y Cooperación (14-16/11/2018); XXXII Congreso Internacional de Economía Aplicada, ASEPELT (4-7/07/2018), entre otros.
Keywords: Eurasia - Situación económica; Unión económica euroasiática; Asociación estratégica; Comercio bilateral; Modelo gravitatorio